ANALISIS PENGARUH KONDISI LINGKUNGAN WORKSHOP KERJA BANGKU TERHADAP MOTIVASI BELAJAR MAHASISWA DI PROGRAM STUDI PENDIDIKAN TEKNIK MESIN FKIP UNIVERSITAS SEBELAS MARET - Aloisius Satriya Gusnadi; Nyenyep Sriwardani (Nozel : Jurnal Pendididikan Teknik Mesin, 2025)
Improving the quality of vocational education, particularly in the field of engineering, is a strategic step in preparing graduates to be competitive in the industrial sector. One crucial factor that supports the learning process is a well-maintained workshop environment. This study aims to analyze the influence of workbench workshop environmental conditions on the learning motivation of students in the Mechanical Engineering Education Program at the Faculty of Teacher Training and Education, Universitas Sebelas Maret. This research employed a quantitative approach with an associative survey design. The sample consisted of 91 students selected through a total sampling technique. Data were collected using a closed-ended questionnaire with a Likert scale (1–4) and analyzed using regression analysis. The results show that the average score for the workshop environment was 41.12, while the average score for learning motivation was 56.80. The normality test indicated that the residual data for learning motivation were normally distributed (Asymp. Sig. = 0.074), and the linearity test confirmed a linear relationship between workshop environment and learning motivation (Sig. = 0.297). The regression test revealed that the workshop environment had a positive influence on student learning motivation. These findings suggest that a well-managed workshop environment can foster enthusiasm and student engagement in the learning process.